The English Learning Training Basics for Sabbangparu Community Youth Through the Lecture Method - Satriani; Inayah, Nur; Hasbi, Muhammad; Novianti, Anggi; Firmah, Andi (Education and Talent Development Center of Indonesia, 2022)
Basic English language learning in the community is one of the community service initiatives that try to provide English language learning. This project was overseen by As'Adiyah Sengkang, an English lecturer at FTK IAI. One of the activities carried out during the program was the presentation of basic English material using the lecture method. The lecture method has various advantages, including allowing lecturers to convey material in a more appealing manner, such as by utilizing personal pronouns, greetings, and introductions. Based on the results of this training, it is a new reference for other teachers to use in every program of formal, informal, and non-formal educational institutions. Furthermore, because this strategy is recognized as a simple method of teaching, young people can do peer tutoring with youth who have not yet had the opportunity to participate in the program. The establishment of community cooperation for the learning of advanced and basic English is another result of implementation.